Implementation of Pancasila Values in Civil Society Participation Against Covid-19 - Nugroho, Bimo Aryo; Hanita, Margaretha (PUSKAPSI Law Review, 2021)
Covid-19 pandemic significantly affects the community’s social life. It does not only result in a health crisis but also an economic crisis. This condition requires a collaboration between the governments and the community as national integration. Recent political situation exhibits a decrease in the tense relationship between the state and the civil society. A transformation is necessary to compromise. Accordingly, the state and civil society should cooperate, help each other, and control each other. Pancasila, as an open ideology, should be implemented as a national life guideline to obtain the state goals amid this pandemic.